Inventory of Gastro-Tourism Ecosystem Concept in Ciletuh Geopark, Indonesia - Abdillah, Fitri; Ayuningsih, Sri Fajar; Basalamah, Anwar; Rachmat, Timotius Agus (E-Journal of Tourism; Volume 12 Number 1 (March 2025)DO - 10.24922/eot.v12i1.125583, 2025)
Ciletuh Geopark has a unique local gastronomic potential that supports food security, namely Hanjeli ( Coix lacryma-jobi ). To maximize the potential and opportunities for local gastronomy development, a gastro-tourism ecosystem is needed to develop.  This study aims to identify key components, assess potential, observe current conditions, and opportunities for developing a sustainable gastro-tourism ecosystem. The research was conducted in Hanjeli Tourism Village, Waluran District, Sukabumi. The descriptive qualitative method with thematic and narrative analysis are needed to explain the findings. Primary data were collected through focus group discussions, in-depth interviews, and documentation analysis. The research findings indicate that Ciletuh possesses a highly promising and distinctive value proposition for establishing a gastro-tourism ecosystem.  There are 12 sub ecosystems that have been inventoried and there are 4 sub ecosystems that are ready to support the ecosystem, namely product value, tourism offerings, destination appeal, and marketing strategies. However, key components such as the income, investment, human resources, infrastructure, and supporting industries require greater attention and involvement from various stakeholders.  The conclusion obtained shows that high effort is needed in developing gastro-tourism in Ciletuh. The most important thing to start developing an ecosystem is raising public awareness of the existing tourism products and values, which is essential for fostering a sustainable gastro-tourism ecosystem in Ciletuh.